The Stress of Caring—Resilience and HPA-Axis Activity in Hair Samples of Youth Residential Caregivers - Bürgin, David; Kind, Nina; Schröder, Martin; Clemens, Vera; Fegert, Jörg M.; Eckert, Anne; Buchheim, Anna; O'Donovan, Aoife; Boonmann, Cyril; Schmid, Marc (Frontiers in Psychiatry, 2020)
Background: Professional caregivers in youth residential care institutions experience frequent verbal and physical aggression as well as multiple stressors as part of their everyday work, leading to high levels of burnout and staff turnover. Resilience might buffer against psychophysiological stress response and therefore be crucial for well-being in professional caregivers. Objectives: We aimed to investigate if measures related to resilience (sense of coherence [SoC], self-efficacy and self-care) and attachment security of caregivers were cross-sectionally associated with stress markers in hair samples (cortisol and dehydroepiandrosterone [DHEA]). Method: Participants (n=134; 64.2% women) reported on individual resilience measures and provided hair samples for cortisol and DHEA assays. Attachment was assessed in a subsample using the Adult Attachment Projective Picture System (AAP, n=69). Linear regression models were fitted to estimate the association between resilience measures and the Cortisol:DHEA ratio, cortisol and DHEA, controlling for gender and age. Results: SoC was associated with a lower Cortisol:DHEA ratio (=-.36, p < .001), driven by a positive association between SoC and DHEA levels (=.28, p=.002). Self-care was also associated with lower Cortisol:DHEA ratios (=-.24, p=.005), due to self-care being associated with higher DHEA (=.21, p=.016). HPA-axis measures were not associated with self-efficacy nor with attachment patterns in a subsample. Conclusions: Our findings imply that youth residential care institutions might benefit from programs focusing on enhancing SoC and self-care practices. Fostering a meaningful, comprehensible and manageable professional climate in caregiving environments and implementing self-care in routine practices might enhance not only well-being but also physical health of professional caregivers and in this way buffer adverse health effects of chronic stressors.